Bilateral trade among the Developing Eight (D-8) countries / Mohim Sheihaki Tash - Tash, Mohim Sheihaki (2013)
The Developing 8 (D-8) is a group of predominantly Muslim developing countries that are all members of the Organization of Islamic Conference (OIC), which have formed an economic alliance. It consists of Bangladesh, Egypt, Indonesia, Iran, Malaysia, Nigeria, Pakistan and Turkey. The group was established after an announcement in Istanbul Turkey on June 15, 1997. The group is designed to gradually reduce tariffs on specific goods between member-states, with a supervisory committee overseeing the process. The purpose of the group is to reduce barriers to free trade between member states, as well as promote inter-state cooperation. Despite the important role of D-8 countries, the empirical literature analyzing the trade of D-8 members with each other is still rather limited. Thus, it is interesting to investigate the trade among these countries in depth. This dissertation investigates the intra-trade of the preferential trade agreement among the D-8 countries by looking at the possibility of full-fledged trade liberalization through the expansion of the coverage of the preferential tariff reduction. This study applies the gravity modeling approach using panel data in two stages – before and after formation of D-8 cooperation –for a quantitative analysis of the economic effects of a preferential trade arrangement between the contracting countries. An important aim of the research is to appraise whether there will be significant gains in intra-trade amongst the D-8 member countries when tariff barriers and enhancement measures are being entirely dismantled. The composition of trade determines the level of bilateral matching of commodities of an exporter with the demands of an importer. Obviously, the gravity model does not take into account commodity composition. Instead, we employ the trade intensity index to show the effect of commodity composition on bilateral trade. Using the decomposition method, similar to Drysdale (1967), we aim to show how much of the trade volume effect is due to complementarity (compositional effect) and country bias (average resistance). It is expected that an index that captures the composition of trade could provide better understanding of the effect of trade costs on bilateral trade flows. The results indicate that all the variables used in the model have the expected sign and are significant. In summary, the results signify that while D-8 intra-trade is expected to increase very substantially, not all countries will experience a welfare gain under a free trade arrangement. Likewise, the impact on the economic sector differs substantially across countries. The findings of this thesis may serve as recommendations for policy makers to improve the bilateral trade flows amongst the D-8 countries as important trading partners.